Pendampingan Produksi Konten Digital pada Media Lokal SuaraBanyuurip.com sebagai Langkah Penguatan Strategi Konten dan Integrated Marketing Communications (IMC) - Mugito (Program Studi Ekonomi Pembangunan, 2026)
Abstract The advancement of digital technology has significantly transformed public information-consumption patterns. The shift in audience preference from long-form text-based news toward fast, accessible visual content has contributed to declining interest in in-depth reporting and has affected the popularity of local news media. At the same time, competition has intensified with the rise of homeless media and content aggregators on platforms such as Instagram and TikTok, which frequently disseminate information without adhering to journalistic verification standards. These dynamics compel local media outlets, including Suarabanyuurip.com, to adapt by employing more creative and audience-responsive communication strategies. This study aims to analyze the impact of changing information-consumption preferences on readership levels and the competitive position of Suarabanyuurip.com, as well as to formulate Instagram- and TikTok-based content marketing strategies integrated with the principles of Integrated Marketing Communications (IMC). These strategies are intended to strengthen brand awareness, enhance interest in long-form news content, and improve the competitiveness of local media in the digital era. The research employs a descriptive qualitative approach through content observation and literature review. The findings indicate that news visualisation, content-format adaptation based on platform characteristics, and message consistency through IMC constitute effective strategies for increasing audience reach, engagement, and loyalty toward local media. This study offers theoretical contributions to the development of Content Marketing and IMC scholarship within the context of local journalism and provides practical benefits for Suarabanyuurip.com in designing more adaptive and sustainable communication strategies.